A low-evaporation coated glass storage bottle and a preparation method thereof
Patent Information
- Application Number
- CN202611246713.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的在于提供一种低析出镀膜玻璃储存瓶及其制备方法,以解决现有技术中镀膜层与玻璃基体的结合力不足,导致在长期使用过程中引发碱金属离子的析出的技术问题
1、本发明通过氨基芳基膦酸类化合物自组装形成的界面层,在玻璃瓶体与复合镀膜层之间构建了稳固的化学和物理双重连接,界面层中的膦酸基通过共价键将氨基芳基膦酸类化合物分子牢固锚定于玻璃瓶体表面,氨基作为连接位点与复合镀膜层结合,在玻璃瓶体与复合镀膜层之间建立了稳固的共价键连接,实现了膜层与玻璃基体的牢固结合与长期稳定,同时,界面层中苯环作为疏水基团在界面层内部形成疏水环境,进一步增强了界面层的化学稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of coated glass bottle technology, and in particular to a low-precipitation coated glass storage bottle and its preparation method. Background Technology
[0002] Glass possesses excellent thermal stability, chemical stability, optical properties, and mechanical properties, making it an excellent packaging and storage material. With the development of industries such as microelectronics and high-end chemical reagents, the requirements for packaging containers such as glass storage bottles for large quantities of high-purity, high-value chemicals are becoming increasingly stringent.
[0003] Common surface treatments for the inner surfaces of glass storage bottles mainly include frosting and siliconization. However, due to increasingly stringent requirements for controlling ion deposition in glass storage bottles, traditional processes are no longer sufficient to meet the requirements for controlling the deposition of metal ions and other impurities on the inner surface of glass storage bottles. Therefore, the industry is gradually shifting towards coating the inner surface of glass storage bottles with inorganic oxide films as a barrier layer, aiming to inhibit the migration of alkali metal ions through physical isolation.
[0004] However, in the existing technology, the adhesion between the coating layer and the glass substrate is insufficient, and the coating layer may have defects such as pinholes, cracks or uneven thickness. This can cause water molecules or solutions to penetrate to the glass surface through these defects during long-term use, leading to the precipitation of alkali metal ions. Summary of the Invention
[0005] The purpose of this invention is to provide a low-precipitation coated glass storage bottle and its preparation method, so as to solve the technical problem in the prior art that the adhesion between the coating layer and the glass substrate is insufficient, which leads to the precipitation of alkali metal ions during long-term use.
[0006] The technical problem to be solved by this invention can be achieved through the following technical solution: A low-precipitation coated glass storage bottle includes a glass bottle body, wherein an interface layer and a composite coating layer are sequentially disposed on the inner and outer surfaces of the glass bottle body. The interface layer is formed on the surface of the glass bottle by the self-assembly of aminoarylphosphonic acid compounds, and the thickness of the interface layer is 0.5-2 nm. The composite coating layer is a SiO2 / TiO2 composite film layer.
[0007] Preferably, the aminoarylphosphonic acid compounds include at least one of aminobenzylphosphonic acid compounds and aminophenylphosphonic acid compounds.
[0008] Preferably, the aminobenzylphosphonic acid compounds include at least one of 4-aminobenzylphosphonic acid and α-aminosubstituted benzylphosphonic acid.
[0009] Preferably, the aminophenylphosphonic acid compounds include at least one of 2-aminophenylphosphonic acid, 3-aminophenylphosphonic acid, and 4-aminophenylphosphonic acid.
[0010] Preferably, the SiO2 / TiO2 composite film comprises TiO2 and SiO2 in a molar ratio of 1:(5-20).
[0011] Preferably, the composite coating layer comprises 2 to 4 layers of SiO2 / TiO2 composite film layers stacked together, and the thickness of the composite coating layer is 100 to 300 nm.
[0012] Preferably, the raw material for the composite coating layer includes a composite coating solution; the composite coating solution is obtained by mixing titanium dioxide sol and silica sol. The raw materials for preparing titanium dioxide sol include tetrabutyl titanate, organic solvent, chelating agent and deionized water; the raw materials for preparing silica sol include tetraethyl orthosilicate, organic solvent, deionized water and acid.
[0013] Preferably, the chelating agent includes at least one of acetylacetone, benzoylacetone, and citric acid.
[0014] More preferably, the molar ratio of tetrabutyl titanate to chelating agent is 1:(0.8-1.2).
[0015] More preferably, the pH of the silica sol is 2.5-3.5.
[0016] Preferably, the acid includes at least one of hydrochloric acid, nitric acid, and sulfuric acid.
[0017] Preferably, the organic solvent includes at least one of anhydrous ethanol, methanol, and isopropanol.
[0018] Through the above technical solution, an interface layer and a composite coating layer are sequentially provided on the inner and outer surfaces of the glass bottle. The interface layer serves as an intermediate layer to connect the glass bottle and the composite coating layer. The interface layer is formed by the self-assembly of an aminoaryl phosphonic acid compound. Its molecular chain contains phosphonic acid groups, benzene ring structural units, and amino groups. The phosphonic acid groups are located at one end of the molecular chain and are distributed on the side of the interface layer close to the surface of the glass bottle, serving as anchoring groups to anchor the entire molecule to the surface of the glass bottle.
[0019] Phosphonic acid groups exhibit highly selective chemisorption on the silanol groups of glass surfaces, forming stable PO-Si covalent bonds through dehydration condensation. Simultaneously, the dihydroxyl structure of phosphonic acid groups enables bidentate anchoring, enhancing interfacial bonding strength. In contrast, amino groups, under self-assembly conditions, can only form unstable hydrogen bonds or electrostatic adsorption with silanol groups, failing to achieve effective anchoring. Amino groups tend to solubilize towards the solution side, while phosphonic acid groups competitively replace the surface hydration layer and bind to silanol groups. Therefore, driven by both thermodynamics and kinetics, phosphonic acid groups actively accumulate on one side of the glass surface and achieve chemical anchoring. The benzene ring, constrained by its rigid structure and intermolecular π-π stacking, arranges itself orderly within the interfacial layer, forming a hydrophobic environment, while the amino group is exposed on the upper surface of the interfacial layer as a bonding site. The phosphonic acid groups, benzene rings, and amino groups together achieve robust anchoring and functional partitioning of the interfacial layer on the glass surface.
[0020] The benzene ring is distributed inside the interface layer, forming a hydrophobic environment as a hydrophobic group. This hydrophobic environment works in conjunction with the physical barrier function of the composite coating layer to prevent water molecules from migrating and penetrating to the surface of the glass bottle, thereby improving the water resistance of the inner surface of the glass bottle and controlling the precipitation of alkali metal ions on the inner surface of the glass bottle. At the same time, the benzene ring, as a rigid structural unit, provides structural rigidity to the interface layer and maintains the structural stability of the interface layer. The amino group is located at the other end of the molecular chain, exposed on the upper surface of the interface layer, and serves as a bonding site to bind with the composite coating layer.
[0021] More preferably, the aminoarylphosphonic acid compound is an aminobenzylphosphonic acid compound.
[0022] Aminobenzylphosphonic acid compounds contain methylene segments in their molecular chains, with the methylene group located between the phosphonic acid group and the benzene ring, distributed as flexible segments in the interface layer. Due to the difference in thermal expansion coefficients among the glass bottle body, the rigid benzene ring structure in the interface layer, and the composite coating layer, thermal stress will be generated between the layers under the temperature changes during the high-temperature curing stage of the preparation process and subsequent use. The flexible methylene segments can effectively absorb and dissipate the thermal stress accumulated at the interface through conformational adjustment and internal rotation of the molecular chain segments, playing a stress buffering role and significantly improving the thermal stability and long-term reliability of the coated glass storage bottle.
[0023] A method for preparing a low-precipitation coated glass storage bottle includes the following steps: S1. Clean the glass bottle and perform surface hydroxylation activation treatment; S2. Immerse the glass bottle after step S1 in a solution of aminoarylphosphonic acid compound with a concentration of 1-3 mmol / L for 12-48 hours at a temperature of 20-50°C. Then, heat-treat the glass bottle at 100-220°C for 1-3 hours under an inert gas atmosphere to obtain a glass bottle containing an interface layer. S3. Immerse the glass bottle containing the interface layer into the composite coating solution, pull it out at a speed of 1-5 mm / s, dry it at 80-120℃, repeat the operation 1-3 times, and finally cure it at 350-550℃ for 5-20 min to form a composite coating layer, thus obtaining a low-precipitation coated glass storage bottle.
[0024] Preferably, the surface hydroxylation activation treatment is oxygen plasma treatment with a power of 100-300W and a treatment time of 2-10min.
[0025] Through the above technical solution, after cleaning and activation treatment, silanol active sites are formed on the glass surface, while surface organic contaminants are removed, providing a clean reaction surface for the self-assembly of the interface layer. The activated glass bottle is then immersed in a solution of aminoarylphosphonic acid compounds. The aminoarylphosphonic acid molecules chemically adsorb onto the silanol groups on the glass bottle surface through phosphonic acid groups, spontaneously arranging themselves to form a self-assembled monolayer on the glass bottle surface.
[0026] In this process, aminoarylphosphonic acid compounds are initially anchored to the glass surface via hydrogen bonds formed by phosphonic acid groups and silanol groups. Then, through heat treatment, they are converted into PO-Si covalent bonds for firm anchoring. Molecules spontaneously arrange themselves into an ordered structure through π-π stacking and van der Waals forces. Phosphonic acid groups are oriented and concentrated on one side of the glass surface, while amino groups are exposed on the outside, and benzene rings are distributed within the interface layer. In the resulting interface layer, phosphonic acid groups are bonded to the glass bottle surface via PO-Si covalent bonds, the benzene rings form a hydrophobic environment within the interface layer, and the amino groups serve as bonding sites exposed on the interface layer surface for bonding with the composite coating layer.
[0027] A glass bottle containing an interface layer is immersed in a composite coating solution, and a composite film is formed on the surface of the interface layer through immersion dip coating. During the immersion coating process, SiO2 / TiO2 sol particles in the composite coating solution uniformly cover the upper surface of the interface layer, and amino groups are exposed on the upper surface of the interface layer. The lone pair electrons on the nitrogen atoms of the amino groups form hydrogen bonds or coordination bonds with the sol particles in the composite coating solution, connecting the composite coating layer and the interface layer. During the drying process, the solvent in the composite coating solution evaporates, the concentration of SiO2 / TiO2 sol particles gradually increases, the distance between particles shortens, and dehydration condensation reactions occur between the uncondensed hydroxyl groups on the surface of adjacent sol particles, forming Si-O-Si, Ti-O-Ti, and Si-O-Ti bonds, achieving preliminary cross-linking between particles. At the same time, further condensation reactions occur between the sol particles and the exposed amino groups and residual silanol groups on the surface of the interface layer, establishing a preliminary chemical bond between the composite film layer and the interface layer. As the solvent evaporates, the crosslinking density between sol particles and between particles and the interface layer gradually increases, forming a three-dimensional network structure film with a certain thickness. During the curing process, as the temperature rises to 450℃, the residual organic groups in the composite film undergo thermal decomposition and removal, and the Si-OH and Ti-OH in the composite film further condense, making the Si-O-Ti network structure more complete and increasing the density of the film.
[0028] Thus, the interface layer achieves a strong bond between the glass bottle and the composite coating layer through the chemical anchoring of phosphonic acid groups, the hydrophobic barrier of benzene rings, and the interfacial connection of amino groups. At the same time, the hydrophobic environment provided by the benzene rings acts as a chemical hydrophobic barrier, which, together with the dense physical structure of the SiO2 / TiO2 composite film layer itself, forms a dual synergistic protection system to prevent water molecules from migrating and penetrating to the surface of the glass bottle, thereby effectively inhibiting the precipitation of alkali metal ions in the glass bottle.
[0029] The beneficial effects of this invention are: 1. This invention establishes a robust chemical and physical dual connection between the glass bottle body and the composite coating layer through an interface layer formed by the self-assembly of aminoarylphosphonic acid compounds. The phosphonic acid groups in the interface layer firmly anchor the aminoarylphosphonic acid compound molecules to the surface of the glass bottle body through covalent bonds. The amino groups act as bonding sites and combine with the composite coating layer, establishing a robust covalent bond connection between the glass bottle body and the composite coating layer. This achieves a strong bond and long-term stability between the film layer and the glass substrate. At the same time, the benzene ring in the interface layer acts as a hydrophobic group, forming a hydrophobic environment inside the interface layer, further enhancing the chemical stability of the interface layer.
[0030] 2. This invention achieves synergistic protection through the chemical anchoring of the interface layer and the physical barrier of the coating layer. The SiO2 / TiO2 composite film itself has a dense physical structure, which can act as the first physical barrier to prevent water molecules from migrating and penetrating to the glass bottle surface. At the same time, the hydrophobic environment provided by the benzene ring in the interface layer acts as the second chemical barrier, forming a hydrophobic interface between the composite coating layer and the glass bottle, further reducing the adsorption of water molecules. The two work synergistically to prevent water molecules from reaching the glass surface, thereby inhibiting the ion exchange reaction between alkali metal ions and water molecules at the source and effectively reducing the precipitation of alkali metal ions. Detailed Implementation
[0031] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0032] Example Example 1: A method for preparing a low-precipitation coated glass storage bottle, comprising the following steps: S1. The glass bottle is subjected to high-pressure water rinsing, alkaline cleaning solution (potassium hydroxide: ethylenediaminetetraacetic acid: stearic acid: deionized water = 1:0.3:0.2:9) ultrasonic cleaning at 100kHz for 15 minutes at 50℃, high-pressure water rinsing, acidic cleaning solution (potassium hydroxide: glycerol: citric acid: fatty acid glycerides: deionized water = 1:0.3:3:0.4:18) ultrasonic cleaning at 80kHz for 15 minutes at 30℃, and finally rinsed with ultrapure water. The cleaned glass bottle is then subjected to oxygen plasma treatment at 200W for 5 minutes and dried in a clean environment for later use. S2. Dissolve 4-aminobenzylphosphonic acid in methanol to prepare a 2 mmol / L solution. Completely immerse the glass bottle treated in step S1 in this solution and allow it to stand at 25°C for 24 hours. After removal, heat at 150°C for 2 hours under nitrogen protection. Clean with methanol using ultrasonication for 15 minutes to remove physically adsorbed excess molecules. S3. Tetrabutyl titanate, anhydrous ethanol, acetylacetone, and deionized water are mixed in a molar ratio of 1:5:1:3 and stirred for 4 hours to obtain titanium dioxide sol. Tetraethyl orthosilicate, anhydrous ethanol, and deionized water are mixed in a molar ratio of 1:8:4, and the pH is adjusted to 3 with hydrochloric acid. The mixture is then stirred and hydrolyzed in a 50°C water bath for 4 hours, followed by aging for 24 hours to obtain acidic silica sol. The titanium dioxide sol and silica sol are mixed at a TiO2:SiO2 molar ratio of 1:10 and stirred until homogeneous to obtain a composite coating solution. The glass bottle treated in step S2 is completely immersed in the composite coating solution for 10 minutes. It is then lifted out at a speed of 3 mm / s and dried at 100°C for 20 minutes. This immersion and drying process is repeated twice. The glass bottle is cured at 450°C for 10 minutes to form a composite coating layer. After cooling, it is ultrasonically cleaned with ultrapure water for 20 minutes and dried to obtain a low-precipitation coated glass storage bottle.
[0033] Example 2 The only difference between this embodiment and Embodiment 1 is that in step S3, titanium dioxide sol and silica sol are mixed at a TiO2:SiO2 molar ratio of 1:5.
[0034] Example 3 The only difference between this embodiment and Embodiment 1 is that in step S3, titanium dioxide sol and silica sol are mixed at a TiO2:SiO2 molar ratio of 1:20.
[0035] Example 4 The only difference between this embodiment and Embodiment 1 is that the immersion and drying operations are repeated 3 times in step S3 to make the total thickness of the composite coating layer reach 300nm.
[0036] Example 5 The only difference between this embodiment and Embodiment 1 is that only one dip-coating and drying operation is performed in step S3, so that the total thickness of the composite coating layer reaches 100nm.
[0037] Example 6 The only difference between this embodiment and Example 1 is that the concentration of the 4-aminobenzylphosphonic acid solution in step S2 is 3 mmol / L.
[0038] Example 7 The only difference between this embodiment and Example 1 is that the concentration of the 4-aminobenzylphosphonic acid solution in step S2 is 1 mmol / L.
[0039] Example 8 The only difference between this embodiment and Embodiment 1 is that 4-aminobenzylphosphonic acid in step S2 is replaced with an equal amount of 4-aminophenylphosphonic acid.
[0040] Comparative Example Comparative Example 1: A method for preparing a low-precipitation coated glass storage bottle, comprising the following steps: S1. The glass bottle is subjected to the following steps in sequence: high-pressure water rinsing, alkaline cleaning solution (potassium hydroxide: ethylenediaminetetraacetic acid: stearic acid: deionized water = 1:0.3:0.2:9) ultrasonic cleaning at 100kHz for 15 minutes at 50℃, high-pressure water rinsing, acidic cleaning solution (potassium hydroxide: glycerol: citric acid: fatty acid glycerides: deionized water = 1:0.3:3:0.4:18) ultrasonic cleaning at 80kHz for 15 minutes at 30℃, and finally rinsed with ultrapure water. The cleaned glass bottle is then subjected to oxygen plasma treatment at 200W for 5 minutes and dried in a clean environment for later use. S2. Tetrabutyl titanate, anhydrous ethanol, acetylacetone, and deionized water are mixed in a molar ratio of 1:5:1:3 and stirred for 4 hours to obtain titanium dioxide sol. Tetraethyl orthosilicate, anhydrous ethanol, and deionized water are mixed in a molar ratio of 1:8:4, and the pH is adjusted to 3 with hydrochloric acid. The mixture is then stirred and hydrolyzed in a 50°C water bath for 4 hours, followed by aging for 24 hours to obtain acidic silica sol. The titanium dioxide sol and silica sol are mixed at a TiO2:SiO2 molar ratio of 1:10 and stirred until homogeneous to obtain a composite coating solution. The glass bottle treated in step S2 is completely immersed in the composite coating solution for 10 minutes and then lifted out at a speed of 3 mm / s. It is then dried at 100°C for 20 minutes. The immersion and drying process is repeated twice. The glass bottle is cured at 450°C for 10 minutes to form a composite coating layer. After cooling, it is ultrasonically cleaned with ultrapure water for 20 minutes and dried to obtain a low-precipitation coated glass storage bottle.
[0041] Comparative Example 2 The only difference between this comparative example and Example 1 is that SiO2 sol is not prepared in step S3, but only titanium dioxide sol is used as the single coating liquid, and only a TiO2 film layer is deposited on the surface of the interface layer.
[0042] Comparative Example 3 The only difference between this comparative example and Example 1 is that TiO2 sol is not prepared in step S3, but only silica sol is used as the single coating liquid, and only SiO2 film is deposited on the surface of the interface layer.
[0043] Performance testing 1. Film adhesion: Tested according to GB / T9286-2021. Each embodiment and comparative example was tested 5 times using the same method, and the average value was taken.
[0044] 2. Water resistance test: (1) Alkali leaching amount: Tested according to GB / T4548-2026. Each example and comparative example were tested 5 times using the same method, and the average value was taken.
[0045] (2) High-temperature and high-humidity alkali leaching test: The coated glass storage bottle was placed in a constant temperature and humidity chamber; the temperature was set at 50℃ and the relative humidity at 95%; it was left for 168 hours, and then naturally cooled to room temperature. The surface condition of the film was observed. The test was conducted according to GB / T4548-2026. Each example and comparative example was tested 5 times using the same method, and the average value was taken.
[0046] 3. Film thickness test: The test was conducted according to GB / T40279-2021. Each example and comparative example was tested 5 times using the same method, and the average value was taken.
[0047] The results of the above experiments are shown in Table 1: Table 1. Performance test results of the examples and comparative examples.
[0048] Based on Example 1 and Comparative Example 1, it can be seen that in Comparative Example 1, the SiO2 / TiO2 composite coating layer adheres to the glass surface only through physical adhesion and limited hydrogen bonding, resulting in weak adhesion. Under high temperature and humidity conditions, water molecules penetrate to the glass surface through microscopic defects in the composite coating layer, initiating an ion exchange reaction between alkali metal ions in the glass and water molecules. The H+ in the water molecules... + The water migrates into the glass network. This process simultaneously increases the pH near the glass surface, and the alkaline environment further corrodes the glass network. Due to insufficient interfacial adhesion, the composite coating gradually loses its adhesion and peels off under the dual effects of continuous water molecule penetration and glass surface erosion. In Example 1, the interface layer is firmly anchored to the glass surface by forming PO-Si covalent bonds between phosphonate groups and silanol groups on the glass surface. The hydrophobic barrier of the benzene ring further reduces the adsorption of water molecules on the glass surface, inhibiting the ion exchange reaction at its source. Therefore, even if trace amounts of water molecules reach the interface in a high-temperature and high-humidity environment, the anchored phosphonate groups can capture the Na+ migrating from the glass in situ. + This breaks the vicious cycle and ensures that the membrane remains unshed after high temperature and high humidity tests.
[0049] As shown in Example 1 and Comparative Example 2, the TiO2 film has a dense physical structure and can act as a physical barrier to prevent water molecule penetration. However, the ability of a single TiO2 film to block alkali metal ions in glass is limited. Although the TiO2 film is dense, once ion exchange reactions occur on the glass surface, Na+... +It is still possible for the TiO2 film to migrate outward through grain boundaries or defects. In Comparative Example 2, although the phosphonic acid groups in the interface layer can anchor the TiO2 film to the glass surface, the TiO2 film experiences significant shrinkage stress during curing, making it prone to microcracks and resulting in a decrease in its barrier effect. In Example 1, SiO2 was introduced to form a composite film. SiO2 has excellent alkali metal ion barrier properties, and the bridging oxygen bonds in its network structure can effectively block Na+. + Simultaneously, SiO2 and TiO2 form Si-O-Ti chemical bonds at the interface, enabling the two phases to be uniformly composited at the nanoscale. This retains the compactness of TiO2 while leveraging the ion-barrier function of SiO2, reducing pinholes and cracks that may occur in monolayer films. Therefore, the alkali leaching amount of the SiO2 / TiO2 composite film is significantly lower than that of a single TiO2 film.
[0050] Based on Examples 1 and 3, it is evident that the SiO2 film exhibits good chemical stability and alkali metal ion barrier properties, but its physical density is lower than that of the TiO2 film. The network structure formed by the condensation of SiO2 sol during curing is relatively loose, allowing water molecules to more easily penetrate the glass surface through the micropores in the film. In Comparative Example 3, although the introduction of the interface layer improved the film's adhesion compared to the sample without an interface layer, the loose structure of the single SiO2 film made it more susceptible to water molecule penetration in high-temperature and high-humidity environments. This led to continuous ion exchange reactions on the glass surface, causing the film to gradually detach due to corrosion products accumulating at the interface. In Example 1, TiO2 was introduced to form a composite film. The TiO2 nanoparticles filled the micropores in the SiO2 network structure, significantly improving the density of the composite film. Simultaneously, Si-O-Ti chemical bonds formed in the SiO2 / TiO2 composite film, with the two phases cross-linking at the molecular scale to form a denser network structure. Therefore, the physical barrier function of the composite film is better than that of the single SiO2 film. After the high temperature and high humidity test, the increase in alkali leaching was only 20%, which is far lower than the 73% of the comparative example 3, and the film did not fall off.
[0051] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A low-precipitation coated glass storage bottle, comprising a glass bottle body, characterized in that, An interface layer and a composite coating layer are sequentially provided on the inner and outer surfaces of the glass bottle. The interface layer is formed on the surface of the glass bottle by the self-assembly of an aminoarylphosphonic acid compound, and the thickness of the interface layer is 0.5-2 nm. The composite coating layer is a SiO2 / TiO2 composite film layer.
2. The low-precipitation coated glass storage bottle according to claim 1, characterized in that, The aminoarylphosphonic acid compounds include at least one of aminobenzylphosphonic acid compounds and aminophenylphosphonic acid compounds.
3. The low-precipitation coated glass storage bottle according to claim 1, characterized in that, The SiO2 / TiO2 composite film comprises TiO2 and SiO2 in a molar ratio of 1:(5-20).
4. The low-precipitation coated glass storage bottle according to claim 1, characterized in that, The composite coating layer consists of 2 to 4 layers of SiO2 / TiO2 composite film layers stacked together, and the thickness of the composite coating layer is 100 to 300 nm.
5. A low-precipitation coated glass storage bottle according to claim 1, characterized in that, The raw material for the composite coating layer includes a composite coating solution; the composite coating solution is obtained by mixing titanium dioxide sol and silica sol. The raw materials for preparing the titanium dioxide sol include tetrabutyl titanate, organic solvent, chelating agent and deionized water; the raw materials for preparing the silica sol include tetraethyl orthosilicate, organic solvent, deionized water and acid.
6. A low-precipitation coated glass storage bottle according to claim 5, characterized in that, The chelating agent includes at least one of acetylacetone, benzoylacetone, and citric acid.
7. A low-precipitation coated glass storage bottle according to claim 5, characterized in that, The acid includes at least one of hydrochloric acid, nitric acid, and sulfuric acid.
8. A low-precipitation coated glass storage bottle according to claim 5, characterized in that, The organic solvent includes at least one of anhydrous ethanol, methanol, and isopropanol.
9. A method for preparing a low-precipitation coated glass storage bottle, used to prepare the low-precipitation coated glass storage bottle according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Clean the glass bottle and perform surface hydroxylation activation treatment; S2. Immerse the glass bottle after step S1 in a solution of aminoarylphosphonic acid compound with a concentration of 1-3 mmol / L for 12-48 hours at a temperature of 20-50°C. Then, heat-treat the glass bottle at 100-220°C for 1-3 hours under an inert gas atmosphere to obtain a glass bottle containing an interface layer. S3. Immerse the glass bottle containing the interface layer into the composite coating solution, pull it out at a speed of 1-5 mm / s, dry it at 80-120℃, repeat the operation 1-3 times, and finally cure it at 350-550℃ for 5-20 min to form a composite coating layer, thus obtaining a low-precipitation coated glass storage bottle.
10. The method for preparing a low-precipitation coated glass storage bottle according to claim 9, characterized in that, The surface hydroxylation activation treatment is an oxygen plasma treatment with a power of 100-300W and a treatment time of 2-10min.